Electronic fetal monitoring concepts and applications - Menihan, Cydney Afriat, 1951-; Kopel, Ellen; Ovid Technologies, Inc. (Philadelphia : Wolters Kluwer, 2019)
'The newly updated Electronic Fetal Monitoring: Concepts and Applications, 3rd Edition, is an invaluable guide for clinicians (nurses, nurse-midwives, physicians) responsible for ordering, initiating, performing, and interpreting electronic fetal monitoring (EFM). Written by OB/GYN nurses and advanced practitioners, this combination textbook/workbook offers clinicians involved in perinatal care a uniquely detailed, in-depth, and historical perspective on EFM. Topics include maternal-fetal physiology, EFM instrumentation, antepartum and intrapartum fetal assessment and pattern interpretation, and a variety of additional issues and challenges relevant to the current state of EFM practice. Applicable to both the novice and seasoned practitioner, this text is useful as a both a primer for this specialty field and also as a detailed resource to ready for the NCC Certificate of Added Qualification in EFM. Upgrade and update your EFM skills with: Examples of EFM tracings that demonstrate the points presented in the text- including 22 case studies annotated with real-time bedside interpretation, followed by expert review with commentary to support these analyses. Validation of knowledge - New! End-of-chapter study questions and answers are a perfect supplement for certification exam preparation. For the educator, methods of competence validation are discussed and presented in detail. Up-to-date EFM guidelines - explained and demonstrated in real-life, situational context. Concise, easy-to-follow support for optimal acquisition and assessment of EFM data, and proper response to findings. Expert advice on handling both clinical and instrumental challenges related to EFM. Detailed explanation of the workings of EFM equipment and technology. Proven algorithms for management of antepartum testing and of EFM data, outlining specific interventions and their rationales. Coverage of crucial knowledge, including maternal-fetal physiology of fetal heart rate patterns and management of unusual EFM tracings, common problems and more. Chapter features include helpful tips ('Stork Bytes') to highlight important points. Your book purchase includes a complimentary download of the enhanced eBook for iOS, Android, PC, and Mac. Take advantage of these practical features that will improve your eBook experience: The ability to download the eBook on multiple devices at one time--providing a seamless reading experience online or offline. Powerful search tools and smart navigation cross-links that allow you to search within this book, or across your entire library of VitalSource eBooks Multiple viewing options that enable you to scale images and text to any size without losing page clarity, as well as responsive design. The ability to highlight text and add notes with one click. About the Clinical Editors, Cydney Afriat Menihan, CNM, MSN, RDMS, is a Nurse Midwife and Perinatal Consultant in North Kingstown, Rhode Island. Ellen Kopel, RNC, MS, is a Nurse Educator and Perinatal Consultant in Tampa, Florida'--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Fetal Monitoring -- methods; Heart Rate, Fetal -- physiology; Fetal heart rate monitoring